Disk Cooling and Wind Lines as Seen in the Spectral Line Evolution of V960 Mon - Adolfo Carvalho; Lynne Hillenbrand; Jerome Seebeck (The Astrophysical Journal, 2023)
We follow up our photometric study of the postoutburst evolution of the FU Ori object V960 Mon with a complementary spectroscopic study at high dispersion that uses time series spectra from the Keck/HIgh Resolution Echelle Spectrograph. Consistent with the photometric results reported in Carvalho et al., we find that the spectral evolution of V960 Mon corresponds to a decrease in the temperature of the inner disk, driven by a combination of a decreasing accretion rate and an increasing inner disk radius. We also find that although the majority of the absorption lines are well matched by our accretion disk model spectrum, there are several strong absorption line families and a few emission lines that are not captured by the model. By subtracting the accretion disk model from the data at each epoch, we isolate the wind and outflow components of the system. The residuals show both broad and highly blueshifted profiles, as well as narrow and only slightly blueshifted profiles, with some lines displaying both types of features.